The effect of adding Kaempferia galanga on different dosages of artificial feed on the growth of milk fish seed (Chanos chanos) - Linayati Linayati; Tri Yusufi Mardiana; Muhammad Zulkham Yahya; Awaliyah Feni Furoidah (Departemen Akuakultur FPIK UNDIP, 2022)
This research was carried out from 25th October to 5th December 2021 at the Brackish and Marine Water Laboratory, Faculty of Fisheries, Pekalongan University. The purpose of this study was to determine the effect of adding kencur (Kaemferiagalanga) to feed on milkfish growth. The study used laboratory experimental methods with 4 treatments and 3 replications. The treatments used were A (0% or feed without kencur), B (2% kencur powder/100g feed), C (4% kencur powder/100g feed) and D (6% kencur powder/100g feed). The results showed that treatment B gave the highest growth yield of 8.59g, followed by treatment C 4.95g, treatment D 3.78g and the lowest was treatment A, namely 3.78g. After analyzing the variance, the results of the F count are greater than the F table, which means that the addition of kencur to feed has an effect on the growth of milkfish. Survival rate of fish during treatment for all treatments was 100%. The water quality during the study was still within a reasonable range, namely temperature 28 -30 C, salinity 18-20 ppt, pH 7.5-7.9 and DO 4.6 - 5 ppm.Keyword: Milkfsih, Kaempferia galanga, Growth